Analysis Analysis of the Effect of BOPO, CAR, DPK, LDR, and NPL on the Financial Performance of Banking Companies on the IDX 2021-2023 - Rakadewa, Vinsensius Agus; Ambarwati, Sri Dwi Ari; Hikmah, Khoirul (CV. Strata Persada Academia, 2025)
This study examines the impact of financial ratios—Operating Expenses to Operating Income (BOPO), Capital Adequacy Ratio (CAR), Third Party Funds (DPK), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL)—on the financial performance of banking companies listed on the Indonesian Stock Exchange (IDX) during the post-COVID-19 recovery period (2021–2023). The research adopts a quantitative descriptive approach, utilizing multiple linear regression analysis on data collected from banks meeting specific criteria within the study period. The findings reveal that BOPO significantly and negatively affects Return on Assets (ROA), highlighting operational inefficiencies that erode profitability. CAR also exhibits a negative impact, suggesting that the emphasis on regulatory compliance and capital adequacy post-pandemic may hinder credit expansion and productive investment. Conversely, DPK and NPL show no significant influence on ROA, attributed to idle funds and effective credit risk mitigation measures. While indicative of efficient fund distribution, LDR negatively affects ROA due to heightened credit risk and operational costs during the economic recovery. This study contributes to the understanding of banking sector dynamics in Indonesia during a critical recovery phase, providing insights into optimizing financial performance through improved operational efficiency and strategic fund allocation. The results highlight the importance of balancing regulatory compliance, risk management, and profitability in the evolving economic landscape.